Viability of Chemical Modification of Thermoplastic Starch with Citric Acid Through Reactive Extrusion - Cinthia S. Diniz; Patterson P. de Souza; Patrícia S.O. Patrício (Materials Research)
This study evaluates the feasibility of modifying thermoplastic starch using citric acid through extrusion processing. The samples were characterized by FTIR, TGA, XRD, and tensile testing. In the FTIR analysis, carbonyl group formation was observed, indicating esterification between the starch hydroxyl groups and the carboxyl groups of the acid. TGA provided data on the thermal events in the materials. In the tensile test, Young's modulus increased while elongation at break decreased, making the modified starches more rigid and less ductile. XRD analysis revealed structural changes due to the increased acid concentration and the presence of plasticizer. Esterification was effective at citric acid concentrations of 1.0 to 2.5–3.0 wt%, but difficulties in processing and controlling process parameters were noted, as highlighted in previous studies. These results demonstrate the viability of starch modification, although challenges remain in controlling production and achieving the desired characteristics.